2002
DOI: 10.1034/j.1600-6143.2002.20902.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicities of Immunosuppressive Agents

Abstract: Cardiovascular disease is one of the major causes of morbidity and mortality following solid organ transplantation. Many of the current immunosuppressive drugs are associated with an increase of one or more risk factors for the development of atherosclerosis. This review compares the mechanism by which individual immunosuppressive agents may impact on these risk factors and the differential contribution of cyclosporine, tacrolimus, mycophenolate, azathioprine, and Rapamycin to these individual risk factors. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
261
3
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(273 citation statements)
references
References 115 publications
3
261
3
6
Order By: Relevance
“…Diabetic transplant recipients are at increased risk for cardiovascular disease (2,3) and exhibit higher mortality (1,4 -6) and reduced graft survival (7,8) compared with nondiabetic transplant recipients. Current therapies for maintenance immunosuppression have adverse effects on BP (9,10), lipids (9,10), and glycemic control (11)(12)(13)(14)(15) in RTR, thus contributing to increased cardiovascular morbidity and mortality. More selective immunosuppressive therapies without the cardiovascular and metabolic toxicities of current therapies may therefore improve outcomes in diabetic RTR.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic transplant recipients are at increased risk for cardiovascular disease (2,3) and exhibit higher mortality (1,4 -6) and reduced graft survival (7,8) compared with nondiabetic transplant recipients. Current therapies for maintenance immunosuppression have adverse effects on BP (9,10), lipids (9,10), and glycemic control (11)(12)(13)(14)(15) in RTR, thus contributing to increased cardiovascular morbidity and mortality. More selective immunosuppressive therapies without the cardiovascular and metabolic toxicities of current therapies may therefore improve outcomes in diabetic RTR.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent single-center study, cardiovascular events and malignancy were the most common causes of death after 5 yr of transplantation in patients with a functioning kidney (8). While there are differences in the side effect profile between cyclosporine and tacrolimus, therapy with CNI contributes to several cardiovascular risk factors, including hypertension, hyperlipidemia, and metabolic abnormalities such as hyperglycemia and hyperuricemia (9). In addition, nephrotoxicity from CNI may also contribute to cardiovascular disease.…”
Section: Calcineurin Inhibitors Minimization Regimensmentioning
confidence: 99%
“…However CNI-based immunosuppression is associated with complications that result in posttransplant morbidities that may limit further improvement in long-term outcome (8,9). While nephrotoxicity has been amply documented and is frequently cited as the Achilles' heel of the CNI representing toxicity-limiting efficacy, the proof of inexorable progression of CNI-induced nephrotoxicity remains controversial (28 -31) In a recent review of data from the Scientific Registry of Transplant Recipients, Ojo et al (30) reported that 15.7% of recipients of extrarenal organs developed renal insufficiency within 5 yr of transplantation.…”
Section: Calcineurin Inhibitors Minimization Regimensmentioning
confidence: 99%
“…nephrotoxicity (Platz et al, 1994), cardiovascular disease (Miller, 2002) and cancer progression (Hojo et al, 1999). Therefore, the development of a novel immunosuppressant with less patient burden has eagerly been awaited.…”
Section: Introductionmentioning
confidence: 99%